2013
DOI: 10.1007/s10549-013-2666-z
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of the Oncotype Dx breast cancer assay in clinical practice: a systematic review and meta-analysis

Abstract: The impact of the Oncotype Dx (ODX) breast cancer assay on adjuvant chemotherapy (ACT) treatment decisions has been evaluated in many previous studies. However, it can be difficult to interpret the collective findings, which were conducted in diverse settings with limited sample sizes. We conducted a systematic review and meta-analysis to synthesize the results and provide insights about ODX utility. Studies, identified from PubMed, Embase, ASCO, and SABCS, were included if patients had ER+, node –, early-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(113 citation statements)
references
References 47 publications
8
98
2
Order By: Relevance
“…30,[47][48][49] However, the widespread use of this test has come into question recently, as the literature has suggested that certain cases might be risk stratified more costeffectively using histopathologic variables. [50][51][52][53][54] Our data support this. The Magee equations, along with histologic and immunohistochemical criteria, may be a more cost-effective alternative in identifying cases that would likely stratify into a high or low Oncotype DX risk-stratification category.…”
Section: Modern Pathology (2015) 28 921-931supporting
confidence: 86%
“…30,[47][48][49] However, the widespread use of this test has come into question recently, as the literature has suggested that certain cases might be risk stratified more costeffectively using histopathologic variables. [50][51][52][53][54] Our data support this. The Magee equations, along with histologic and immunohistochemical criteria, may be a more cost-effective alternative in identifying cases that would likely stratify into a high or low Oncotype DX risk-stratification category.…”
Section: Modern Pathology (2015) 28 921-931supporting
confidence: 86%
“…Data have shown that the recurrence score was low in 48% of the first 20,050 tested patients and in this group there is minimal, if any, benefit from adjuvant chemotherapy (32,33). On the other hand, current knowledge indicates that approximately up to 77% of breast cancer patients may be exposed to chemotherapy toxicity and costs with little or no clinical benefit (34). Given the remaining ~30% of 'unnecessary' chemotherapies, these existing tests are still far from ideal.…”
Section: Alcam Ihc Results ------------------------------------------mentioning
confidence: 99%
“…Recently, classification of breast cancer subtypes based on HER2 expression as well as ER and PR status was performed to determine the appropriate treatment and to predict the patient's prognosis [23] . In addition, it was shown that the expression patterns of several genes clinically correlate with the outcome of adjuvant therapy and the prognosis of breast cancer patients [24] . Thus, gene expression profiling will provide a new taxonomy of breast cancer.…”
Section: Hormone-dependent Cancer and Endocrine Therapymentioning
confidence: 99%